The Truman White House The Administration of the Presidency 1945 -1953 - Heller, Francis H. (University Press of Kansas, 1980)
This retrospective study brings together twentytwo key associates of President Truman's to consider the administrative operation of the presidency from 1945 to 1953. A record of the discussions that took place at the conference held in May 1977 sponsored by the Harry S. Truman Library Institute for National and international Affairs, it presents an assortment of views on Truman's administrative philosophies and practices.The contributors are persons who were close to Truman throughout his presidency: members of the cabinet, the White House staff, and senior officials in Executive Office agencies. Sharing personal reflections are, among others, Charles Brannan, W. Averell Harriman, Leon H. Keyserling, Charles S. Murphy, Richard E. Neustadt, John W. Snyder, Elmer B. Staats, and the late Tom C. Clark. Coordinating the interaction with incisive questions and comments on general administrative history are Edward H. Hobbs of Auburn University, Dorothy Buckton James of the Virginia Polytechnic Institute and State University, Louis W. Koenig of New York University, and Chester A. Newland of the University of Southern California.A number of important administrative aspects of Truman's presidency are touched upon as the participants review the years of their White House experience. They talk about policy making in the areas of national security and foreign affairs, about budget and economic matters, relations with Congress, domestic problems such as civil rights, presidential appointments, and even press relations. They exchange anecdotes about the president's style and their working relationships with him in staff meetings, cabinet meetings, and private briefing sessions. They consider whether Truman had a chief of staff or the equivalent and debate the "liberal" versus the "conservative" stance of the Truman presidency. The creation of the Central Intelligence Agency and the establishment of the National Security Council, the Council of Economic Advisers, and the National Security Resources Board during Truman's administration clearly improved and strengthened the organization of and the institutional aids to the presidency. In answer to the question of what can be learned from the way Truman operated the presidency, however the overriding theme of the exchanges recorded here is that the style of the White House is-inescapably-the president's style.The picture that emerges in the pages of life and work in Truman's administration is one of informality, enthusiasm, and camaraderie. A familylike atmosphere pervaded the staff, and the president played the crucial role in setting the tone. Thus, the White House between 1945 and 1853 was orderly because Harry Truman was an orderly person; it was profoundly human because that was Truman's way. Truman is remembered by his key associates as a prodigious worker and a thorough professional.To those who wrote and spoke for this volume there is no question that the nation was well served by the way Harry Truman managed his affairs in the White House. Incorporating a broad spectrum of firsthand information on the administrative concepts and practices of the Truman era, this book will be of prime interest to all students of government and executive organization.